A Systematic Literature Review on Security Challenges in Cloud–Edge Hybrid Systems - Adarsh Kumar Mishra; Shubham Kamlesh Mishra (International Journal of Wireless Security and Networks, 2026)
Cloud–edge hybrid systems have become a key framework in today’s distributed computing landscape, combining fast, near-source data processing at the edge with the flexible scalability and resource richness of centralized cloud infrastructures. However, this in- tegration introduces a complex security landscape where tradi- tional perimeter- based cloud security measures are insufficient for resource- constrained and physically exposed edge nodes. This literature review synthesizes findings from established research publications (2020–2025), focusing on threat models, vulnerabilities, and mitigation mechanisms across cloud–edge environments. Specifically, we analyze the shift toward Zero Trust Architectures (ZTA) and Lightweight Cryptography as essential defense mechanisms. The review identifies critical gaps in unified security frameworks, secure data offloading, and cross-layer trust establishment. Our analysis, supported by recent attack statistics, concludes that future work must prioritize AI-driven threat detection and standardized hybrid security protocols.
Keywords: AI Threat Detection; Cloud-Edge Computing; Lightweight Cryptography; Zero Trust Architec- ture; hybrid cloud; network security